2005
DOI: 10.1073/pnas.0407159102
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of coactivator complex assembly and function by protein arginine methylation and demethylimination

Abstract: Nuclear receptors activate transcription by recruiting multiple coactivators to the promoters of specific target genes. The functional synergy of the p160 coactivators [steroid receptor coactivator-1, glucocorticoid receptor interacting protein (GRIP1), or the activator for thyroid hormone and retinoid receptors], the histone acetyltransferases cAMP response element binding protein binding protein (CBP) and p300 and the histone methyltransferase coactivator-associated arginine methyltransferase (CARM1) depends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
184
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(192 citation statements)
references
References 34 publications
8
184
0
Order By: Relevance
“…Since mass spectrometry of the protein after 2 h in the presence of either PAD2 or PAD4 revealed that both mono-and dimethylated arginines remained (Figure 6a), it suggested that deimination 5,27 of the methylated arginine did not occur. [28][29][30] Consistent with our data, Raijmakers et al 31 showed that the human, mouse and rabbit PAD enzymes were not able to 'reverse' the methylation of arginine residues by converting monomethylated arginine into citrulline in synthetic peptides. These authors showed that the human and mouse PAD enzymes can only convert non-methylated peptidylarginine into peptidylcitrulline in vitro.…”
Section: Identification Of Arginyl Residues Deiminatedsupporting
confidence: 89%
“…Since mass spectrometry of the protein after 2 h in the presence of either PAD2 or PAD4 revealed that both mono-and dimethylated arginines remained (Figure 6a), it suggested that deimination 5,27 of the methylated arginine did not occur. [28][29][30] Consistent with our data, Raijmakers et al 31 showed that the human, mouse and rabbit PAD enzymes were not able to 'reverse' the methylation of arginine residues by converting monomethylated arginine into citrulline in synthetic peptides. These authors showed that the human and mouse PAD enzymes can only convert non-methylated peptidylarginine into peptidylcitrulline in vitro.…”
Section: Identification Of Arginyl Residues Deiminatedsupporting
confidence: 89%
“…Alternatively, Suv4-20h1 could modify nonhistone factors. Indeed, CARM1 that methylates H3R17 also targets specific arginine residues in CBP/p300 (29,30). The related enzyme PRMT1 methylates H4R3 (31) and also modifies the PolyA-binding protein NAB2p (32).…”
Section: Discussionmentioning
confidence: 99%
“…Because we previously reported that F-amidine could antagonize this effect in vivo (17) and because Cl-amidine displays enhanced in vitro potency, we evaluated its ability to interfere with the PAD4-mediated enhancement of the p300GBD-GRIP1 interaction. For these studies, we utilized a previously described mammalian two-hybrid assay that monitors the efficiency of the p300GBD-GRIP1 interaction as well as the effects of PAD4 on this system ( Figure 5) (17,23). Briefly, CV-1 cells were transiently transfected with plasmids encoding a luciferase reporter construct, p300GBD fused to the Gal4 DNA binding domain, the p300 binding domain of GRIP1 (i.e., the AD1 domain) fused to the VP16 activation domain (AD), and either wildtype PAD4 or the catalytically defective C645S mutant.…”
Section: In Vivo Studies With Cl-amidinementioning
confidence: 99%
“…Of these various pathways, the best characterized is its incompletely defined role in human gene regulation. For example, PAD4 deiminates multiple transcriptional regulators, including p300, a histone acetyltransferase (HAT) (23) that acts as a transcriptional coactivator, and histones H2A, H3, and H4 (24,25). Interestingly, the deimination of p300 and the histone proteins appears to have opposite effects on transcriptional regulation; i.e., the modification of p300 enhances its ability to activate the expression of an artificial reporter construct (23), whereas the deimination of histones H3 and H4 represses the expression of genes under the control of the estrogen receptor (20,21).…”
mentioning
confidence: 99%